Ferromagnetic Order in 2D Layers of Transition Metal Dichlorides - Aguirre, Andrea; Pinar Solé, Andrés; Soler Polo, Diego; González-Orellana, Carmen; Thakur, Amitayush; Ortuzar, Jon; Stesovych, Oleksandr; Kumar, Manish; Peña-Díaz, Marina; Weber, Andrew; Tallarida, Massimo; Dai, Ji; et al. (Advanced materials (Deerfield Beach, Fla.), 2024)
Magnetism in two dimensions is traditionally considered an exotic phase mediated by spin fluctuations, but far from collinearly ordered in the ground state. Recently, 2D magnetic states have been discovered in layered van der Waals compounds. Their robust and tunable magnetic state by material composition, combined with reduced dimensionality, foresee a strong potential as a key element in magnetic devices. Here, a class of 2D magnets based on metallic chlorides is presented. The magnetic order survives on top of a metallic substrate, even down to the monolayer limit, and can be switched from perpendicular to in-plane by substituting the metal ion from iron to nickel. Using functionalized STM tips as magnetic sensors, local exchange fields are identified, even in the absence of an external magnetic field. Since the compounds are processable by molecular beam epitaxy techniques, they provide a platform with large potential for incorporation into current device technologies.
Keywords: ferromagnetism; 2D material; van der waals material; XMCD; nickelocene; transition metal halides